Preliminary zero-dimensional thermodynamic analysis of a gas turbine using EBSILON Professional software - Bokisz, Kamil; Ruziewicz, Adam; Cholewiński, Maciej (Archives of Thermodynamics, 2026)
The application of zero-dimensional mathematical modelling offers significant advantages in the domain of energy systems. Firstly, it serves as a crucial support tool for the design process. Secondly, it facilitates the optimisation of operating parameters, thereby enhancing the efficiency of energy systems. Furthermore, it offers, depending on the accuracy of a model, a comprehensive analysis of the impact of various factors on the performance of a specific system. The present article focuses on a model of a gas turbine unit that has been developed using the EBSILON Professional software. The model was employed to assess the operating parameters that are characteristic of gas turbines, including the turbine inlet temperature and compression ratio, that are crucial for the efficiency and unit power of the abovementioned power system. Moreover, this approach enables the determination of the optimal operating points for the considered assumptions. Next, for the selected case, an analysis was conducted to determine the impact of changes in atmospheric air parameters on the operation of the gas turbine, applying two different approaches. Research has demonstrated that daily, and particularly seasonal, fluctuations in temperature can exert a substantial influence on the efficiency and capacity of the system, while fluctuations in pressure and relative humidity have a much smaller impact on turbine operation. Finally, the simplified model was utilised to ascertain the effect of incorporating hydrogen into fuel on the operational parameters of a gas turbine, indicating the effect of both quantitative and qualitative changes of stream in the combustion chamber and turbine.